(untitled) (Bangladesh Journal of Botany, 2015)
An endemic wild balsam, Impatiens munnarensis Barnes restricted to Idukki district of Kerala, India has been rediscovered from a new locality Megamalai hills, Tamil Nadu, India after 78 years. The detailed description of the taxa is provided in the presented paper. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21678 Bangladesh J. Bot. 43(2): 227-229, 2014 (September)